Jet dynamics of a cavitation bubble near unequal-sized dual particles - Jinsen Hu; Jingfei Duan; Yifan Liu; Jiaxin Yu; Yuning Zhang; Dan Gao; Yuning Zhang (Ultrasonics Sonochemistry, 2024)
The jet dynamics of a cavitation bubble near unequal-sized dual particles is investigated employing OpenFOAM, and the effects of the jets on the particles are quantitatively analyzed in terms of their pressure impacts. Different from single-particle cases, the necks that evolve between dual particles are closely linked to the formation mechanism of the jets. Based on the simulation results, the jet dynamics can be divided into five scenarios: (1) the contraction of the annular depression produced by the collision of the two necks causes the bubble to split into two daughter bubbles and generates a single jet inside each daughter bubble; (2) the annular depression impacts the particle, leading to the bubble to fracture and producing a single jet inside a daughter bubble; (3) the bubble is split by a single neck constriction and produces a single jet; (4) the bubble is split by a single neck constriction and generates two jets; and (5) the bubble is split by the contraction of two necks and produces four jets together with three daughter bubbles. As the bubble–particle distance or the radius ratio of the dual particles increases, the maximum force on the small particle generated by the bubble decreases.